KONTESKTUALISASI HADIS PERLOMBAAN BERHADIAH DALAM PERSPEKTIF SYUHUDI ISMAIL (Thobaqot: Jurnal Ilmu Hadis, 2024)
This research provides a hadith perspective regarding prize competitions in the historical and contemporary context of Islam. Using qualitative methods and a social-historical approach, this research uses the takhrij hadith bilafdz}i method in the book of Polar al-Tis'ah using the thoughts of Syuhudi Ismail. The results of this research show that Islam allows this type of competition, especially those that contain elements of jihad. Prizes are allowed to be taken if there is a muhallil, and are not allowed if there is no muhallil. Ulama also interpret the hadith text of the race as a parable to support jihad fii sabilillah. In contextualizing current prize competitions, the research concludes that taking prizes is permitted if the type of competition is in accordance with Islamic law and the prize is free from betting or gambling elements. For example, in the Musabaqa>h Tilawatil Qur'a>n (MTQ) competition which is considered in accordance with Islamic law, promotes knowledge and preserves culture. The importance of jihad fii sabilillah remains the main criterion. Textually, the hadith of prize competitions provides an understanding of Islamic teachings that apply throughout time and place.